Impact of Tax Evasion Among tax Payers of Bale Robe Town Administration, Ethiopia - Hailu, Birhanu; Kechema, Tarik (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2020)
The main purpose of this study was to investigate the impact of tax evasion among tax payers of payers Robe town administration. To attain the intended objective the study used quantitative research method and logit method for the econometrics model. And to collect the necessary data from the respective respondents questionnaire was distributed and collected from 346 respondents. For the data analysis SPSS version 20.0 was used. The finding of this study revealed that; tax knowledge, efficiency of tax authority, equity, and tax audit are found to be significant factors that could affect the tax evasion perception of tax payers.